A Kinetic and electrochemical study of the dissolution of gold in aerated cyanide solutions: the role of solid and solution phase purity - Jeffrey, Matthew I. (Curtin University, 1997)
Over the last 100 Years, the cyanidation process has been the most popular method for recovering gold from its ores. Despite this, there are still efforts to improve the efficiency of the process, particularly as ores become more difficult to treat. Many investigators have studied the cyanidation process, although a large proportion of these studies have obtained contradictory results. This thesis presents a kinetic and electrochemical study of the leaching of gold in cyanide solutions, and emphasis is placed on rationalising the conflicting results which have been published in the past.The leaching rate of gold was measured using a rotating electrochemical quartz crystal microbalance, an instrument which allows the simultaneous measurement of electrochemical data and mass changes at the solid-solution interface in real time. A proportion of this project was devoted to the on-going design of this instrument, and a number of modifications are discussed in detail. Initially, the leaching of gold in cyanide solutions was investigated under conditions of high purity. Under these conditions, it was found that the gold surface is blocked by a passive film, presumably AuCN. The presence of such a film results in the reaction being chemically controlled, and under typical cyanidation conditions (4 mM cyanide, pH 10.0), the rate of dissolution is very low. These kinetic results were supported by complimentary electrochemical studies, which showed that gold is passive in the potential region where cyanidation occurs.The second part of this thesis presents a study of the effect of system purity on the leaching of gold in cyanide solutions. Solution phase purity was investigated by adding controlled amounts of lead or silver to the leach solutions. It was found that in the presence of low concentrations of lead, the dissolution of gold in 20 mM cyanide solutions was oxygen diffusion controlled (as compared to chemical control for gold in the absence of lead). However, high concentrations of lead were found to be detrimental to the leaching process. It is believed that the role of lead is to modify the surface by cementation, hence reducing the effect of the passive film. Silver was also found to be effective at reducing passivation, and the role of silver believed to be similar to that of lead. It was found that unlike lead, high concentrations of silver are not detrimental to the dissolution of gold in cyanide solutions.Solid phase purity was also found to be important in the leaching of gold, and it was found that the leaching of a gold sample which contains 1 % silver is diffusion controlled. This finding is important from an industrial viewpoint, as most native gold contains some silver. Consequently, attempts were made to rationalise the leaching of gold/silver with current plant practice. Discussion on the effect of cyanide and oxygen concentrations, temperature and lead addition is presented.